HUBUNGAN FAKTOR INDIVIDU DAN SAFETY MANAGEMENT PRACTICES TERHADAP PERILAKU KESELAMATAN KARYAWAN PRODUKSI PT ESSENCE INDONESIA (IFF) PLANT KARAWANG TAHUN 2023 - Amanda Khoirunnisa (2023)
Worker safety behavior is essential in preventing work accidents and unwanted incidents, considering the many potential hazards and risks during the PT Essence Indonesia (IFF) production process. This study aims to determine the relationship between individual factors and safety management practices on the safety behavior of production employees. This study used a quantitative method with a cross-sectional design. The study population was 97, so the sample set at 75 was obtained using a purposive sampling technique. The measuring instrument used was a questionnaire, and data were analyzed using chi-square. The results of the study showed that 49.3% of employees had poor safety behavior and concluded that there was a significant relationship between OSH knowledge (p-value=0.004; OR=4.61), OSH awareness (p-value=0.000; OR=7, 64), perception of risk (p-value=0.010; OR=4.53), motivation to behave safely (p-value=0.000; OR=13.96), and safety management practices (p-value=0.004; OR= 4.51) with safety behavior. The company is encouraged to improve worker safety behavior regarding individual factors such as training and drills and safety management practices by providing a forum for conveying perceptions that can increase management commitment.